The effect of trans-ACPD, a metabotropic excitatory amino acid receptor agonist, on the responses of primate spinothalamic tract neurons - Paleček, Jiří; Palečková, V; Dougherty, P.M; Willis, W.D (Pain, 1994)
The responses of primate spinothalamic tract (STT) neurons to innocuous and noxious mechanical stimuli applied to the skin can be enhanced for more than an hour following prolonged noxious stimulation. This increased responsiveness is thought to reflect sensitization of dorsal horn neurons and may help account for secondary hyperalgesia and mechanical allodynia. The proposal that central sensitization is due to the activation of second messenger system was tested in this study by examining the effect of trans-ACPD (trans-D,L-1-amino-1,3-cyclopentanedicarboxylic acid), an agonist of metabotropic excitatory amino acid (EAA) receptors, introduced into the dorsal horn by microdialysis. A low dose of trans-ACPD resulted in an increase in the responses of STT cells to an innocuous mechanical stimulus (BRUSH), but no increase in the responses to noxious mechanical and thermal stimuli or in the excitation produced by iontophoretically applied EAAs. A high dose of trans-ACPD caused a transient increase in background activity, but no change in the responsiveness of spinothalamic cells to any of the test stimuli. It is concluded that low doses of trans-ACPD can selectively enhance transmission through interneuronal pathways mediating tactile inputs to spinothalamic cells.
Keywords: Thalamus; mícha; Amino Acids; Macaca fascicularis; Physical Stimulation; thalamus; Hot Temperature; zvířata; fyzikální stimulace; Action Potentials; Neurons; Neural Pathways; vysoká teplota; receptory metabotropního glutamátu; Microdialysis; aminokyseliny; nervové dráhy; Neurotoxins; Animals; Receptors, Metabotropic Glutamate; Cycloleucine; neurotoxiny; cykloleucin; neurony; Spinal Cord; akční potenciály; mikrodialýza